High hydrostatic pressure processing on microstructure of probiotic low-fat yogurt - Penna, A. L. B.; Subbarao-Gurram; Barbosa-Canovas, G. V. (Elsevier B.V., 2007)
The effect of milk processing on the microstructure of probiotic low-fat yogurt was studied. Skim milk fortified with skim milk powder was subjected to three treatments prior to innoculation: thermal treatment at 85 degrees C for 30 min, high hydrostatic pressure at 676 MPa for 5 min, and combined treatments of high hydrostatic pressure (HHP) and heat. The processed milk was then fermented by using two different starter cultures containing Streptococcus thermophilus, Lactobacillus delbrueckii ssp. bulgaricus, Lactobacillus acidophilus, and Bifidobacterium longum. The microstructure of heat-treated milk yogurt had fewer interconnected chains of irregularly shaped casein micelles, forming a network that enclosed the void spaces. on the other hand, microstructure of HHP yogurt had more interconnected clusters of densely aggregated protein of reduced particle size, with an appearance more spherical in shape, exhibiting a smoother more regular surface and presenting more uniform size distribution. The combined HHP and heat milk treatments led to compact yogurt gels with increasingly larger casein micelle clusters interspaced by void spaces, and exhibited a high degree of cross-linking. The rounded micelles tended to fuse and form small irregular aggregates in association with clumps of dense amorphous material, which resulted in improved gel texture and viscosity. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: high hydrostatic pressure; yogurt; probiotics; microstructure